Studi Eksperimental Kapasitas Lentur Balok Bambu Laminasi (Glue Laminated Bamboo) - Bastian Artanto Ampangallo (Journal on Education, 2023)
This study aims to examine the flexural capacity of bamboo beams through a lamination process using glue. The lamination process is intended to increase the strength and stability of bamboo beams so that they can be used as alternative building materials. In this study, samples of bamboo beams were processed using the lamination method and tested to measure their flexural capacity. The experimental results showed that the largest flexural strength of laminated petung bamboo beams was sample 2 with a value of 124.6312 kg/cm2, while the lowest was sample 3 with a value of 101.2629 kg/cm2, and an average flexural strength with a value of 114 ,2453kg/cm2. From the results obtained, according to PKKI wood laminated petung bamboo for strong class construction, the flexural strength of laminated petung bamboo beams is classified as strong class IV.